Jurnal Penyuluhan: Karakteristik Sosial Demografi dan Faktor Pendorong Peningkatan Kinerja Kader Posyandu - Megawati Simanjuntak (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2014)
Posyandu is one of the community participation approach in health sector that is managed by cadres, with the main problem arises is the declining number of visits of mothers of infants and toddlers.